Attracting social investments through investment platforms: theory and practice ("Journal "U". Economy. Management. Finance.", 2024)
The work is devoted to the study of the role of platform solutions in enhancing social investment in the Russian Federation. The author pays special attention to the definition of existing trends in terms of attracting investments in socially significant projects in Russia, as well as the comparison of domestic and foreign experience in the context of the development of social crowdfunding platforms. As a result, the prospects of this channel for the formation of socially responsible investments were identified, as well as its importance for balanced economic development.
Keywords: investment platforms; social investment; crowdfunding; socially significant projects; sustainable economic development